Effects of rosemary (Rosmarinus officinalis L.) and thyme (Thymus vulgaris L.) essential oils on bone tissue in rats - A.S. Elbahnasawy; E.R. Valeeva (Учёные записки Казанского университета: Серия Естественные науки)
Millions of people around the world suffer from osteoporosis. We need highly effective, safe, and affordable therapeutic agents to help them. Medicinal plants offer a great potential for solving this problem, because they contain many bioactive substances in high concentrations. Of particular value are essential-oil-bearing plants, such as rosemary (Rosmarinus officinalis L.) and thyme (Thymus vulgaris L.). In this research, these two plants were analyzed to identify their effects on the state and formation of the bone tissue in rats. With this aim, we extracted volatile compounds and studied their essential oils using the method of gas chromatography. The results obtained demonstrate that thyme and rosemary monoterpenes effectively inhibit bone resorption. The addition of thyme and rosemary to the diet of rats significantly increased the calcium concentration in their blood plasma and the bone mineral density as compared to the group of rats that were fed a calcium-deficient diet. Notably, thyme bioactive substances have a stronger effect on the bone tissue than rosemary.